Polyphyly of non‐bioluminescent Vibrio fischeri sharing a lux ‐locus deletion - M. S. Wollenberg; S. P. Preheim; M. F. Polz; E. G. Ruby (Environmental Microbiology, 2012)
Summary This study reports the first description and molecular characterization of naturally occurring, non‐bioluminescent strains of Vibrio fischeri . These ‘dark’ V. fischeri strains remained non‐bioluminescent even after treatment with both autoinducer and aldehyde, substrate additions that typically maximize light production in dim strains of luminous bacteria. Surprisingly, the entire lux locus (eight genes) was absent in over 97% of these dark V. fischeri strains. Although these strains were all collected from a Massachusetts (USA) estuary in 2007, phylogenetic reconstructions allowed us to reject the hypothesis that these newly described non‐bioluminescent strains exhibit monophyly within the V. fischeri clade. These dark strains exhibited a competitive disadvantage against native bioluminescent strains when colonizing the light organ of the model V. fischeri host, the Hawaiian bobtail squid Euprymna scolopes . Significantly, we believe that the data collected in this study may suggest the first observation of a functional, parallel locus‐deletion event among independent lineages of a non‐pathogenic bacterial species.

ENSO anomalies over the Western United States: present and future patterns in regional climate simulations - Yongxin Zhang; Yun Qian; Valérie Dulière; Eric P. Salathé; L. Ruby Leung (Climatic Change, 2012)